The Influence of Financial Literacy and Market Orientation on Sustainable Business Competitiveness in Improving UMKM Performance (Study on MSMEs in Malang City) - Insan, Adillah; Nur Rohmad Nuzil (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence of financial literacy and market orientation on sustainable business competitiveness and its impact on the performance of MSMEs in Malang City. MSMEs have a strategic role in the Indonesian economy with a significant contribution to GDP and employment absorption. However, MSMEs still face challenges in financial management and understanding market dynamics. This study uses a quantitative approach with the Partial Least Square (PLS) analysis method. The research sample consists of MSME actors across sectors in Malang City. Data collection was carried out through questionnaires and analyzed with the help of SmartPLS software. The results of the study indicate that financial literacy has a positive and significant effect on sustainable business competitiveness and MSME performance. Likewise, market orientation has a significant effect on MSME competitiveness and performance. Sustainable business competitiveness has also been shown to be a mediating variable that strengthens the relationship between financial literacy, market orientation, and MSME performance. These findings provide important implications for MSME actors, policy makers, and business support institutions. By improving financial literacy and market orientation, MSMEs will be better prepared to face competition and build optimal business sustainability.